2013
DOI: 10.4314/star.v2i2.98894
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Cow Urine Extracts of Selected Plants against Pathogens Causing Rhizome Rot of Ginger

Abstract: The present study was carried out to investigate the inhibitory effect of cow urine extracts of nine plants against two fungi viz., Fusarium aphanidermatum and a bacterium Ralstonia solanacearum rhizome rot of ginger. Antifungal and antibacterial activity of cow urine extracts was investigated by poison food technique and agar extent of growth of test fungi in plates poisoned with extracts was lesser when compared with the control plates. Among fungi, high susceptibility was recorded in case of oxysporum. Cow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 14 publications
2
25
0
7
Order By: Relevance
“…Lithourgidis et al, (2007) observed that soil application of liquid cattle manure (LCM) (excrements plus urine, occasionally containing bedding material) can enhance plant growth and increase crop yield as well as increases in plant macronutrients concentration or uptake. Rakesh et al, (2013) showed that the marked inhibition of rhizome rot pathogens by cow urine extracts of selected plants. The extracts may find a possible use in agriculture as potent agents against pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Lithourgidis et al, (2007) observed that soil application of liquid cattle manure (LCM) (excrements plus urine, occasionally containing bedding material) can enhance plant growth and increase crop yield as well as increases in plant macronutrients concentration or uptake. Rakesh et al, (2013) showed that the marked inhibition of rhizome rot pathogens by cow urine extracts of selected plants. The extracts may find a possible use in agriculture as potent agents against pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we investigated antifungal effect of extracts of different parts of P. longifolia, G. glauca and A. lawii against C. capsici isolated from anthracnose of chilli by poisoned food technique. This technique is widely used to evaluate antifungal activity of a variety of samples including plant extracts (Chutia et al, 2009;Farooq et al, 2010;Rakesh et al, 2013;Kambar et al, 2013). Extracts of P. longifolia exhibited higher inhibition of mycelial growth of C. capsici followed by A. lawii and G. glauca.…”
Section: Discussionmentioning
confidence: 99%
“…The plant materials were dried under shade and powdered in a blender. Cow urine extraction of selected plants was carried out by using the method of Rakesh et al, [15]. with slight modification.…”
Section: Collection Of Cow Urine and Preparation Of Cow Urine Extractsmentioning
confidence: 99%
“…Inhibition of mycelial growth (%) = (C -T / C) x 100, where C and T refers to colony diameter in control and poisoned plates respectively [15].…”
Section: Collection and Identification Of Plantsmentioning
confidence: 99%
See 1 more Smart Citation